Caracterização do complexo de inclusão ropivacaína: β-ciclodextrina - Fraceto, Leonardo Fernandes [UNESP]; Gonçalves, Marcos Moisés; Moraes, Carolina Morales; Araújo, Daniele Ribeiro de; Zanella, Luciana; Paula, Eneida de; Pertinhez, Thelma de Aguiar (Sociedade Brasileira de Química, 2007)
Characteriza of the inclusion complex ropivacaine: β-cyclodextrin. Ropivacaine (RVC) is a widely used local anesthetic. The complexation of RVC with β-cyclodextrin (β-CD) is of great interest for the development of more efficient local anesthetic formulations. The present work focuses on the characterization of the RVC:β-CD complex by nuclear magnetic resonance (NMR). The stoichiometry of the complex is 1:2 RVC:β-CD. DOSY-NMR shows that the association constant is 55.5 M-1. Longitudinal relaxation time results show that RVC changes its mobility in the presence of β-CD. This study is focused on the physicochemical characterization of inclusion complexes that are potentials options for pain treatment.
Characterization of the inclusion complex ropivacaine: β-cyclodextrin
Keywords: ropivacaine; cyclodextrin; NMR